Cross-hedging effectiveness of jet fuel oil spot prices with future contracts - Ahmed, Mohamed Mostafa Elsayed (2023)
This study investigates the cross-hedging performance for jet fuel oil spot prices with four highly correlated commodities' future contracts; namely, NYMEX Light Sweet Crude Oil (WTI), ICE Europe Brent Crude, NYMEX Harbor No. 2 Heating Oil, ICE Europe Low Sulphur Gasoil with four different time frame contracts from one-month maturity up to four-month maturity to estimate an optimal hedge ratio that aviation firms can utilize to hedge away the jet fuel oil prices volatility.